Alternative communication in support of individuals amyotrophic lateral sclerosis (Research, Society and Development, 2021)
Alternative Communication is a communication system that provides individuals, at different stages of life, with the possibility of communicating in different social contexts. Thus, several resources are used to contribute to the individual with Amyotrophic Lateral Sclerosis - ALS, which is a disease characterized by deterioration of motor neurons and causes progressive paralysis of skeletal muscles, compromising limb motricity, swallowing, breathing and speech. Speech impairment plays a fundamental role in the patient's quality of life as well as that of their caregiver. The Amplified Alternative Communication (AAC) appears as an opportunity to alleviate the communication limitations imposed by the disease, due to the difficulties presented by the disease, means that facilitate the continuity of daily activities are necessary. The present work aims to analyze alternatives, for the expression of thought, to a person who is prevented, due to the disease, from establishing effective oral, written or signed verbal communication. The research methodology consists of an integrative bibliographic research, through the analysis of theories, present in various sources, such as scientific articles, prepared between the years 2012 to 2021. Furthermore, the research can be characterized as of qualitative nature in which the results of other scientific productions on the subject are subjectively analyzed. As the research identified, the Extended Alternative Communication can be considered a facilitating intervention in social interaction and in the quality of life of patients with Amyotrophic Lateral Sclerosis.